Methodological quality, guidance, and tools in scoping reviews: a scoping review protocol. Issue 4 (25th April 2022) - Pollock, Danielle; Tricco, Andrea C.; Peters, Micah D.J.; Mclnerney, Patricia A.; Khalil, Hanan; Godfrey, Christina M.; Alexander, Lyndsay A.; Munn, Zachary
ABSTRACT: Objective: The objective of this scoping review is to identify and report on evidence (such as guidance) or tools regarding methodological quality or risk of bias of scoping reviews. Introduction: Scoping reviews have gained popularity in recent years but have been criticized for variations in their approaches. This scoping review will examine evidence on the methodological quality of scoping reviews. It will also identify and describe potential methods to inform the development of a tool for appraising the methodological quality of scoping reviews. Inclusion criteria: This review will consider all documents reporting on the development, evaluation, or use of tools addressing the critical appraisal or risk of bias of scoping reviews. The search will seek evidence published from 2005 onwards, corresponding with the publication of Arksey and O'Malley's framework for scoping reviews. Methods: A three-step search strategy will be used to locate both published and unpublished documents. An initial search of MEDLINE identified keywords and MeSH terms. A second search of MEDLINE, Embase, and CINAHL will follow. Google and Google Scholar will be searched for difficult-to-locate and unpublished literature. The authors will use their professional networks, social media accounts, and professional newsletters to contact methodologists to obtain any additional materials. Documents will be independently screened, selected, and extracted by two researchers, and the data will be presented in tables.